Production of glucose-galactose syrup and milk minerals from Greek yogurt acid whey. Issue 21 (20th October 2022) - Lindsay, Mark J.; Molitor, Michael S.; Goculdas, Tejas B.; Zhao, Jikai; Featherman, Jarryd R.; Li, Mengting; Miller, James B.; Avraamidou, Styliana; Rankin, Scott A.; Dumesic, James A.; Huber, George W.
Abstract : A techno-economic analysis and life cycle assessment for the process to produce a sweetener and calcium supplement from Greek yogurt acid whey show that this method has high profitability and a lower environmental footprint than other sweeteners. Abstract : Greek yogurt acid whey (GAW) is a byproduct stream from Greek yogurt production with costly and environmentally unsustainable disposal methods. A process was developed and tested at the benchtop and pilot scale to produce multiple products from GAW. Pilot scale filtration and neutralization operations resulted in the precipitation of calcium phosphate. The large precipitate was harvested via size classification using a hydrocyclone and crushed. The fine precipitate was separated from a lactose-rich stream by membrane filtration and converted to a calcium-rich powder, referred to as milk minerals, in a pilot scale spray dryer. A benchtop process sequence, consisting of acid-catalyzed lactose hydrolysis, filtration, and evaporation, converted the concentrated aqueous lactose filtrate to a sweetener syrup consisting primarily of glucose and galactose. A techno-economic analysis, based on the experimental mass balance data, indicated that the process can be highly profitable (IRR 34.0%) at a GAW inlet of 907 metric tons per day and match the food industry average (IRR 6.25%) at a GAW inlet of 192 metric tons per day GAW. A life cycle assessment demonstrated that the proposed GGS production process had significantly fewer negative environmental impacts than either the production of high fructose corn syrup from corn or sucrose from sugarcane.